THE EFFECT OF PROFITABILITY, LIQUIDITY, AND SOLVENCY ON THE VALUE OF TECHNOLOGY SECTOR COMPANIES LISTED ON THE IDX (2021-2024) - Ariani, Putu Lina Ariani; Musmini, Lucy Sri; Kurniawan, Putu Sukma (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to determine the effect of profitability, liquidity, and solvency on company value. The type of research used is quantitative research with an associative approach. This study uses secondary data sourced from the company's financial statements. The population of this study is all technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period, with a total number of companies in this sector of 47 companies. Sample collection used a purposive sampling technique with the criteria of technology sector companies listed on the IDX consecutively during the 2021-2024 period and having completed financial reports consecutively during the 2021-2024 period. A research sample of 27 companies was obtained with 108 observations. The data analysis technique was carried out using the multiple linear regression analysis method with the help of the IBM SPSS 25 application. The results of this study indicate that partial profitability and liquidity have a positive effect on company value. Solvency has a negative effect on company value.